Analisis Verba Bermakna Menangkap Ikan Pada Bahasa Banjar: Kajian Metabahasa Semantik Alami - Faqih Ijtihadi Rahman; Agus Subiyanto (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study examines the meaning of the verb "to catch fish" in the Banjarese language. It uses the concept of natural semantic metalanguage by Wierzbicka (1997) with the explication analysis technique. Explication is the breakdown of a text whose initial meaning seems implicit to make it explicit. This study explores how cultures from different community groups can have vocabulary with almost similar meanings. This study uses qualitative methods to achieve the elaboration of the meaning of the verbs that appear. The focus of this study is to describe and analyze the meaning of a language using semantic primes so that its basic meaning can be known. The findings show that there are a number of verbs from the Banjarese language that apparently have similar meanings to verbs from other languages. These activity verbs are rooted in the original meaning of doing and happening, both of which are core concepts that describe other meanings. This shows that a language starts from a universal concept. This study also shows that the meaning of verbs that were previously universal can be detailed into various variations with various categories depending on several elements such as the tools used and the location of the activity.